Evaluitis - Eine neue Krankheit - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2006)
"Evaluitis" - i.e. ex post assessments of organizations and persons - has become a rapidly spreading disease. In addition to the well-known costs imposed on evaluees and evaluators, additional significant costs are commonly disregarded: incentives are distorted, ossification is induced and the decision approach is wrongly conceived. As a result, evaluations are used too often and too intensively. A viable and often superior alternative to evaluations is a careful selection of persons and afterwards leaving them to pursue their assigned tasks.
Keywords: D23; D61; H43; M40; M5; 330; Evaluation; Performance; Selection; Research; Incentives